Single step fabrication of antimicrobial fibre mats from a bioengineered protein-based polymer - Costa, André Manuel Abreu (2017)
Genetically engineered protein polymers functionalized with bioactive domains have potential as multifunctional versatile materials for biomedical use. The present work describes the fabrication and characterisation of antimicrobial fibre mats comprising the antimicrobial elastin-like recombinamer (ELR) CM4-A200. The CM4-A200 protein polymer derives from the genetic fusion of the ABP-CM4 antimicrobial peptide from Bombyx mori with 200 repetitions of the pentamer VPAVG. This is the first report on non-crosslinked fibre mats fabricated with an antimicrobial ELR stable in solution. Thermal gravimetric analysis of CM4-A200 fibre mats shows one single degradation step at temperatures above 300 °C, with fibres displaying a higher thermal degradation activation. The electrospun CM4-A200 fibres display high antimicrobial activity against Gram-positive and Gram-negative bacteria with no detectable cytotoxic effects against normal human skin fibroblasts and keratinocytes, revealing the great potential of these polymers for the fabrication of biomedical materials.